Cost Effectiveness of Vacuum-Assisted Closure and Its Modifications: A Review. (21st January 2013) - Hussain, Akhlak; Singh, Kuldip; Singh, Mohinder
Abstract : Negative topical pressure, the general category to which the trademarked VAC therapy belongs, is not a new concept in wound therapy. It is also called subatmospheric pressure therapy, vacuum sealing, vacuum-assisted closure therapy, vacuum pack therapy, and sealing aspirative therapy. The VAC therapy system is trademarked by Kinetic Concepts, Inc., or KCI. It was first reported in 1997. The aim of the procedure is to use negative pressure to create suction, which drains the wound of exudate (i.e., fluid, cells, and cellular waste that has escaped from blood vessels and seeped into tissue) and influences the shape and growth of the surface tissues in a way that helps healing. Negative-pressure therapy for the closure of wounds accelerates secondary wound healing. High cost is still a hindrance in its use in developing nations. Many modifications were tried, but their efficacy is yet to be proved. In reality, this method is quite cost effective. It is only the lack of understanding and adequate setup which makes this method hard to use. The main objective of this paper is to focus on the cost effectiveness of VAC and its modifications. We want to emphasize the importance of homemade NPT and the use of simple suction devices.